Clinical and genetic findings in five female patients with haemophilia A: Identification of a novel missense mutation, p.Phe2127Ser - Martín-Salces, Mónica; Venceslá, Adoración; Alvárez-Román, María Teresa; Rivas, Isabel; Fernández, Ihosvany; Butta, Nora; Baena, Manel; Fuentes-Prior, Pablo; Tizzano, Eduardo F.; Jiménez-Yuste, Víctor (Thrombosis and Haemostasis, 2010)
Severe manifestations of X-linked recessive disorders such as haemophilia A (HA) are rare in females. Here we describe the clinical and genetic findings in five female HA patients from two different Spanish families. Three sisters born to consanguineous parents presented moderate bleeding due to a known mutation (p.Ser1791Pro) detected in a homozygous state. In the second family, two sisters with Morris syndrome (46,XY) and mild/moderate illness were hemizygous for a novel missense mutation, p.Phe2127Ser. The mutation is predicted to impair binding to the factor VIII (FVIII) carrier protein, von Willebrand factor, and thus increased clearance of FVIII from plasma. Clinical and molecular characterisation of these patients is essential to optimise follow-up, genetic counselling and treatment of the disease.
Keywords: Haemophilia A; females; F8 gene; mutations; von Willebrand factor